PENGARUH PROMOSI KESEHATAN DENGAN MEDIA ANIMASI DAN CERITA BERGAMBAR TERHADAP KEMAMPUAN MENDETEKSI BAHAN KIMIA BERBAHAYA DALAM JAJANAN PADA ANAK SEKOLAH DI DESA DANGER - Baiq Fina Farlina; Suhaemi Suhaemi (Media Bina Ilmiah, 2022)
Rhodamine B, Methanil Yellow, Formalin, and Borax are hazardous chemicals that are widely misused in food processing including school snacks are snacks that are often found using these chemicals. This study aims to determine the effect of health promotion with animated media and illustrated stories on children's ability to detect hazardous chemicals in school snacks in Danger Village. This research is a quasi-experimental research (quasi-experimental), with a pretest-posttest control group design. The population of this study were all 5th grade elementary school children in Danger Village, which were taken using cluster random sampling technique. The students were divided into 2 groups, the experimental group would be given education with animation media, while the control group would be given education with illustrated story media (Cergam). Before and after being given treatment, both groups will be given a pretest and posttest to determine the students' ability to detect hazardous chemicals in school snacks. Students' ability to detect hazardous chemicals was measured using cognitive, affective, and psychomotor knowledge tests. Analysis of the data used is the independent test sample t-test.Based on the results of the study, there were posttest differences (sig. value <0.05, i.e. 0.000) in the experimental class and the control class who were given health promotion using illustrated stories and animated videos about hazardous chemicals in food. However, when viewed from the mean value in the control group who was given health promotion through video media, it was higher at 71.12 compared to the mean value in the experimental class who was given health promotion through picture stories